An audit of R&D and commercialization policies, programs and accomplishments of the Industrial Technology Development Institute--Department of Science and Technology - Offemaria, Rodel G. (University of the Philippines Diliman, 2004)
The Industrial Technology Development Institute is one of the 21 agencies under the Department of Science and Technology. It has the largest human resource among DOST's seven research and development institutes, and third overall in the system. ITDI is the oldest government scientific and research agency in the Philippines. It traces its roots to the Bureau of Government Laboratories established by the American colonial rules on July 1, 1901. US scientists provided administrative and research leadership until 1934. What is now ITDI went through several name changes and reorganizations. Until 1987, it has gained, lost and regained numerous functional units and mandates. At the agency level, R&D policies are formulated through multidisciplinary approach. But programs generally mirror the national development line of the political leadership. ITDI's outstanding strength is its intellectual capital. Technical personnel thoroughly outnumber support counterparts over 9 in 10. Over the years, ITDI carried on R&D budget that has apparently restricted its considerable potential to develop product and process technologies, and services that could translate to industrial activities. There are three main R&D activities that ITDI undertake; self-funded, contract, and externally assisted. ITDI funded R&D consistently outnumber the other classifications. Contract and assisted R&D projects provide some financial relief to overall research requirements. Meanwhile, ITDI's patent application performance appears to be hampered by budgetary and technical inadequacies. This would mean lost potential market opportunities and vulnerability to intellectual property infringements. DOST recently introduced a mechanism to strengthen and manage intellectual properties and similar outputs that covers ITDI and all the agencies. The mechanism is designed to also protect and generate maximum benefits from commercialized technologies. The institutional strengths and weaknesses also show the factors and areas where ITDI holds advantages and where it needs improvement. The section on Issues tries to bring out the minor and major problems that afflict the Institute. ITDI survived two World Wars and pestering social upheavals in global and domestic fronts. It had some shining periods in the early decades of the 20th century. It is even credited of spawning some of the basic industries in the country. But until now, it has acquired a reputation as a minor development spark plug in spite its enormous potentials as a supposedly leading research center in the Philippines. The government's commitments to global and regional free trade pacts have put the country and many of its homegrown industries at a serious disadvantage. ITDI's condition is no exception. To become relevant and responsive to the vastly changed domestic and international conditions, ITDI needs to be reassessed in terms of vision, mission, mandate and even organizational culture. In a sense, it cannot continue to play on old rules in a substantially new technology-driven environment characterized by speed, efficiency and productivity.